Efficacy and safety of galcanezumab for prevention of migraine headache in Japanese patients with episodic migraine: A phase 2 randomized controlled clinical trial - Sakai, Fumihiko; Ozeki, Akichika; Skljarevski, Vladimir (Cephalalgia reports, 2020)
Objective: This study was designed to assess the efficacy and safety of galcanezumab in comparison with placebo for the prevention of migraine in Japanese patients with episodic migraine. Methods: In this double-blind, placebo-controlled study, which was conducted over 6 months, randomized adult patients received subcutaneous injections of galcanezumab (120 mg n = 115, 240 mg n = 114) or placebo (n = 230) once monthly. The primary endpoint was the overall mean change from baseline in the number of monthly migraine headache days. The key secondary outcome measures were response rates (≥50%, ≥75%, and 100%); the Migraine-Specific Quality-of-Life Questionnaire Role Function-Restrictive score; monthly migraine headache days requiring acute treatment; and Patient Global Impression of Severity (PGI-S). Results: The mean change from baseline in monthly migraine headache days over months 1–6 was significantly (p < 0.001) greater for the 120-mg galcanezumab dose (−3.60 days) and the 240-mg galcanezumab dose (−3.36 days) compared with placebo (−0.59 days). Both the 120-mg and 240-mg doses of galcanezumab were superior compared with placebo for each of the key secondary endpoints except for PGI-S (only the 240-mg dose was superior). The most commonly reported treatment-emergent adverse events were local injection-site reactions; erythema, swelling, pruritus, and pain were more commonly reported by patients who were treated with galcanezumab than those treated with placebo. Conclusion: The number of monthly migraine headache days was reduced with both doses of galcanezumab, and both doses were safe and well tolerated in Japanese patients with episodic migraine.